Exercise of Innocuous Power by Female Characters in Selected African Prose Fiction Works (Mwanga wa Lugha, 2022)
This study looks at how female characters in Nawaal El Saadawi’s God Dies by the Nile (2007), Mariama Ba’s Scarlet Song (1986), Assia Djebar’s Fantasia: An Algerian Cavalcade (1993), Chinua Achebe’s Anthills of the Savannah (1987)and Bake Robert Tumuhaise’s Tears of my Mother (2013) use non-aggressive types of power to negotiate for social relevance. The study is justified by the fact that African theorists on feminism have increasingly been replacing belligerent ideas found in first and second wave of Western feminism with accommodative versions of African feminisms. The paper therefore seeks to understand how female characters acquire and exercise power without resorting to militancy. Nego-feminism, a coinage of Obioma Nnaemeka, is one such variant of African feminism that forms the theoretical framework of the study. The study located the acquiescent subalternity associated with female characters within the authors’ intention of demonstrating that African feminism is not equivalent to a battle of the sexes but is instead a way of creating complementarity between male and female characters. The paper argues that the form of power exercised by female characters is non-confrontational but nevertheless effective in the creation of a complementary interaction between male and female characters in the texts.